2000
DOI: 10.1024//0170-1789.21.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Normative Geschlechtsrollenorientierung: Entwicklung und Validierung eines Fragebogens

Abstract: Zusammenfassung: Im Rahmen von zwei Studien wurde ein neuer Fragebogen zur Messung normativer Geschlechtsrollenorientierung (NGRO) entwickelt (Studie I) und auf seine Reliabilität und Validität (Studie II) überprüft. Die Erhebung internalisierter, persönlicher Geschlechtsrollennormen (traditionell vs. egalitär) kann im Rahmen der Geschlechterforschung für verschiedenste Fragestellungen von Bedeutung sein. Bereits existierende Fragebögen sind nicht mehr zeitgemäß. Dies führt zu schiefen Scoreverteilungen und ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
40
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 19 publications
5
40
1
Order By: Relevance
“…Similarly, the significant differences in attitudes attributed to educational level confirm previous research (Athenstaedt, 2000;BMFSFJ, 1996;Eckes & Six-Materna, 1999; Zentralarchiv für empirische Sozialforschung, 2000) wherein a higher educational level is associated with more egalitarian attitudes toward gender roles. One possible explanation for this difference is that education generally conveys a liberal attitude and is connected to consciousness-raising, critical thinking, and a widened social awareness.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Similarly, the significant differences in attitudes attributed to educational level confirm previous research (Athenstaedt, 2000;BMFSFJ, 1996;Eckes & Six-Materna, 1999; Zentralarchiv für empirische Sozialforschung, 2000) wherein a higher educational level is associated with more egalitarian attitudes toward gender roles. One possible explanation for this difference is that education generally conveys a liberal attitude and is connected to consciousness-raising, critical thinking, and a widened social awareness.…”
Section: Discussionsupporting
confidence: 87%
“…The differences in attitudes between different subgroups of the sample are consistent with previous research on gender role attitudes: a large body of studies indicated that women are, in general, more egalitarian in their attitudes than men (Athenstaedt, 2000;BMFSFJ, 1996;Brettschneider et al, 1992;Eckes & Six-Materna, 1999;Zentralarchiv für empirische Sozialforschung, 2000). This finding can be explained by the unequal distribution of power and access to resources between the sexes; women have more to gain from egalitarian gender roles and an egalitarian society than men do (Beere et al, 1984;Braun, 2003;Peuckert, 1999).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations